Surgical Approach to Acute Osteochondral Fracture With Patellar Instability in Skeletally Immature Patients - Carlo Coladonato MS; Sean M. Wilson MD; Kevin B. Freedman MD (SAGE Publishing, 2024)
Background: Patellar instability is a common condition that affects many young, active patients and can lead to long-term disability. This video aims to provide insights in the treatment of acute osteochondral fractures in skeletally immature patients after acute patellar dislocation. Indications: Patients who present with acute patellar dislocation and evidence of osteochondral fracture or osteochondral fracture with a loose body are potential candidates for medial patellofemoral ligament reconstruction (MPFLR) with osteochondral fragment fixation. Technique Description: In case 1, arthroscopy revealed a medial patellar facet defect. A medial patellar incision was made with dissection down to the vastus medialis oblique fascia and medial retinaculum. Before continuing to capsulotomy, the dissection for the MPFLR is completed by dissecting down to create a plane between layers 2 and 3. Capsulotomy is then performed with retrieval of the loose body, preparation of the patellar defect, and fixation of the osteochondral fragment. The MPFLR is then performed. An allograft is fixed to the patella with 2 pushlock anchors, and to a distally directed femoral tunnel using a 7-mm pitchfork SwiveLock tenodesis anchor, with care to avoid the medial femoral physis. The capsulotomy is then closed underneath the graft, with layer 2 closed above it. In case 2, a large osteochondral fracture of the lateral femoral condyle with loose cartilage flaps was arthroscopically identified. An anterior incision was made and a lateral lengthening was completed to perform a laterally based arthrotomy to expose the defect on the lateral femoral condyle. The defect site was prepared and the loose body was secured and fixated into the donor site lesion using bioabsorbable screws. The MPFLR was completed as in case 1, and the wound was closed in standard fashion. Results: Acute patellar dislocation with osteochondral fracture has been shown to lower both subjective and functional patient outcome measures. A recent study suggests that in large osteochondral fractures after patella dislocation, internal fixation improves mid- and long-term outcomes when compared with debridement alone. Conclusion: The MPFLR with concurrent osteochondral fracture fixation in patients with open physes is a reliable option for improving patellar stability and protecting articular cartilage from further injury. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form.